(untitled) (World Economics and Finance Bulletin, 2025)
This study aims to identify the consequences of revenue recognition requirements according to IFRS in Iraqi commercial companies and to show the role of standards in giving confidence and credibility to the financial statements of commercial companies. The researchers also used the five steps of applying the standard for the purpose of practical application of the standard research sample, and a sample representing a model of the company’s transactions was selected as sales cases provided by the company to customers to analyze the accounts and determine the differences between them and the standard to come up with the results that show the practical application of the standard and stand on the accounting problemsin the focus of the study. The study reached several conclusions, the most important of which was that the issue of revenue recognition is one of the main accounting concepts that deserve attention and auditing, as it does not represent just a purely technical concept, but rather represents a philosophical basis for thinking about the way economic units deal with income inputs and how to interpret and record them in accounting records